1997
DOI: 10.1148/radiology.202.2.9015078
|View full text |Cite
|
Sign up to set email alerts
|

Saccular intracranial aneurysms: endovascular treatment with mechanical detachable spiral coils.

Abstract: In this relatively small group, endovascular treatment with mechanical detachable spiral coils had a success rate of 90%, and it appears to be a rapid, reliable, and relatively safe technique in the treatment of life-threatening subarachnoid hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Incidence and risk factors 1-1. Incidence The age-adjusted annual incidence of SAH varied 10-fold between different countries, 13) from 1.04 cases per 100,000 population/year in the Middle East 27) to approximately 20 per 100,000/year in Finland 13) and Japan. 12,18,25,28) The sex difference varied between studies; some studies reported no sex difference, 13) while others have reported a higher incidence among women.…”
Section: Using the Guidelinesmentioning
confidence: 99%
See 4 more Smart Citations
“…Incidence and risk factors 1-1. Incidence The age-adjusted annual incidence of SAH varied 10-fold between different countries, 13) from 1.04 cases per 100,000 population/year in the Middle East 27) to approximately 20 per 100,000/year in Finland 13) and Japan. 12,18,25,28) The sex difference varied between studies; some studies reported no sex difference, 13) while others have reported a higher incidence among women.…”
Section: Using the Guidelinesmentioning
confidence: 99%
“…Although the detection rate for small (under 2 mm in diameter) aneurysms may be low, 27,67) it is a highly useful modality for assessing the 3D orientation of vessels around the aneurysm 1,2,9,20,27,33,42,63,64,71) (Grade B). Recently, it has been reported that 3D-CTA is comparable to DSA in the detection of cerebral aneurysm, and that it is even better in providing information for developing surgical strategies.…”
Section: -2 3d-ctamentioning
confidence: 99%
See 3 more Smart Citations